Pengaruh Penggunaan Teknologi dalam Pembelajaran di Dunia Pendidikan Sekolah Dasar - Cindy Nur Miristianti; Indah Sofiatin; Muhammad Iqbal (Yayasan Citra Dharma Cindekia, 2024)
This article examines the positive and negative impacts of technology use in the learning environment of elementary schools. The research highlights greater student engagement through the use of technological devices, creating a more interactive and appealing learning environment. By utilizing digital tools, teachers can present materials more dynamically, facilitate the understanding of concepts, and provide a more comprehensive learning experience. The article further emphasizes that integrating technology into the curriculum can broaden students' access to relevant and up-to-date learning resources. The utilization of educational applications, online platforms, and multimedia can help address learning challenges, enhance students' creativity, and prepare them for the digital era. However, this research also underscores the need for a balanced approach. Integrating technology with traditional teaching methods is crucial to ensuring that education continues to focus on the development of students' intellectual, social, and emotional skills. Therefore, the article emphasizes the necessity of a comprehensive and sustainable educational strategy to optimize the benefits of technology in elementary school learning